Investigation of the association between Pediatric Asthma and Giardiasis; A Cross-Sectional Study on 200 asthmatic children - Fatemeh Behmanesh; Mohammad Hasan Aelami; Zohreh Hassanpour; Zahra Forough; Fariba Berenji; Mohammad Taghi Shakeri; Maryam Khoshkhui (Patient Safety and Quality Improvement Journal)
Introduction:Asthma and parasitic infections are both common childhood diseases. Due to the high prevalence of these two diseases among Iranian children, we decided to investigate the association between giardiasis and asthma and some sociodemographic documents. Materials and Methods: In this study, 200 asthmatic children referred to the asthma clinic of Sheikh Hospital, Mashhad University of Medical Sciences, Mashhad, Iran, and 50 healthy children, as the control group, were included. After interviewing parents, sociodemographic documents were recorded, including age, sex, duration and severity of asthma, parents' education, and occupation. Three-morning stool samples were collected from individuals daily. Examination of giardiasis based directly or formalin-ether based. Giardiasis infection was compared between healthy and asthmatic children. Besides, the relation between sociodemographic documents and giardiasis infection among asthmatic children was investigated. Records were analyzed by statistical package for social sciences (SPSS.ver.20). Results: We found that 12 (6%) samples from the asthma group and 5 (10%) samples from the control group were positive for giardiasis (P=0.13). There was also no significant relationship between the severity or duration of asthma and giardiasis (P=0.33, P=0.97). Besides, there was no significant relationship between sociodemographic documents and giardiasis among asthmatic children (P>0.05).Conclusion: In this study, the frequency of giardiasis was similar in both control and asthma groups. This issue might be probable that giardiasis infection has not any role in protecting, causing, or exacerbating pediatric asthma.